1997
DOI: 10.1165/ajrcmb.16.1.8998073
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p53 mutations in malignant mesotheliomas.

Abstract: Mutations in the p53 gene are the most common genetic alterations found in human malignancies. In this study, a search was done for mutations in the conserved regions of the p53 gene in malignant mesotheliomas. Thirteen malignant mesotheliomas collected over the preceding 12 yr and maintained in paraffin blocks were examined by polymerase chain reaction (PCR) followed by both single-strand conformation polymorphism (SSCP) and denaturing gradient-gel electrophoresis (DGGE). Direct sequence analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 24 publications
1
38
1
1
Order By: Relevance
“…Additionally, nuclear positivity for pSTAT3 has been described in 60% of malignant mesothelioma cases (Achcar Rde et al, 2007). Our data suggest that the involvement of p53 pathway in MPM, typically considered as a wtp53-carrying tumor (Metcalf et al, 1992;Mor et al, 1997), must be further investigated. We show that RNAi-mediated (Figure 6).…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, nuclear positivity for pSTAT3 has been described in 60% of malignant mesothelioma cases (Achcar Rde et al, 2007). Our data suggest that the involvement of p53 pathway in MPM, typically considered as a wtp53-carrying tumor (Metcalf et al, 1992;Mor et al, 1997), must be further investigated. We show that RNAi-mediated (Figure 6).…”
Section: Discussionmentioning
confidence: 77%
“…Mesothelioma most likely has abnormal function of the p53 pathway, e.g. because of mutation or loss of p14ARF (38) or to interaction with simian virus 40 large T antigen (39), even though the tumor often expresses wild-type p53 (20). Thus, as for most tumors, therapeutic approaches successful in p53 inactive cells would be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…chemotherapy or ␥ irradiation) that were not due to up-regulation of TRAIL receptors, DR4 and DR5 (19). In part because mesothelioma is reported to express wild-type p53 (20), we investigated whether p53 was involved in either synergy or in a p53-dependent JNK activation. We found that these cells had nonfunctional p53.…”
mentioning
confidence: 99%
“…3,4 In this malignancy, which is extremely rich in peculiarities, p53 mutations are uncommon. [3][4][5] This certainty may suggest that alterations in the expression of this gene are unlikely to be responsible for either the creation of an MPM phenotype or MPM insensitivity to apoptotic induction itself. In simian virus 40 (SV40)-positive MPM, this occurrence may be explained by an inactivation of the p53 function coming from the viral TAG.…”
Section: T Rmentioning
confidence: 99%